IDENTITIES ON THE epsilon(4n,1)-INTEGRAL TRANSFORM - (:unkn) unknown (UNIV PRISHTINES, 2017)
In the present paper, the authors prove a Parseval-Goldstein type theorem involving the epsilon(4n,1)-generalized exponential integral transform. Then, the theorem is shown to yield a number of new identities involving several well-known integral transforms. Using the theorem and its corollaries, a number of interesting infinite integrals are presented with illustrative examples.
Keywords: epsilon(4n,1)-transform; L-4n-transform; P-4-transform; Laplace transform; Parseval-Goldstein type theorems